Investigation of the Reduction of a Molybdenum/Iron Molecular Nanocluster Single Source Precursor - Andrew Barron (Inorganics, 2018)
The thermolysis of the polyoxometalate cluster [HxPMo12O40⊂H4Mo72Fe30(O2CMe)15O254(H2O)90−y(EtOH)y] (1) under air, argon, and reducing conditions (5%, 10%, 50% H2 with Ar balance) has been investigated. The resulting products have been characterized by XRD, SEM, and EDX analysis. Thermolysis in air at 1100 °C yields predominantly Fe2O3, due to sublimation of the molybdenum component; however, under Ar atmosphere, the mixed metal oxide (Fe2Mo3O8) is formed along with Mo and MoO2. Introduction of 5% H2 (1100 °C) results in the alloy Fe2Mo3 in addition to Fe2Mo3O8 and Mo; in contrast, reduction at a lower temperature (900 °C) yields the carbide (Fe3Mo3C) and the analogous oxide (Fe3Mo3O), suggesting that these are direct precursors of Fe2Mo3. Increasing the H2 concentration (10%) promotes carbide rather than oxide formation (Fe3Mo3C and Mo2C), until alloy formation (Fe7.92Mo5.08) predominates under 50% H2 at 1200 °C. The effect of temperature and H2 concentration on the composition, grain size, and morphology has been investigated by EDX, SEM, and XRD. The relationship of the composition of 1 (i.e., Fe:Mo = 30:84) with the product distribution is discussed.